(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This study examines the framework of neutrosophic F-metric spaces and highlights their role in nonlinear analysis. Within this extended setting, we establish a fixed point theorem that broadens traditional results to the neutrosophic domain. The applicability of the proposed theorem is demonstrated through its use in modeling a satellite web coupling problem. To substantiate the theoretical contributions, we also present concrete examples along with graphical illustrations capturing the nature of the contraction condition